Legal regulation of economic methods to regulate investment relations in the field of environmental protection and use of natural resources - Nurmukhankyzy D.; Ozenbayeva A.T. (Хабаршы. Заң сериясы, 2016)
This article deals with the legal regulation of economic practices in the regulation of investment relations in the field of environmental protection and use of natural resources. We consider the improvement and development of various methods of influence that will stimulate the development of investment activity. Also put forward the issues of economic regulation of environmental protection and nature under the law of the Republic of Kazakhstan.